1989
DOI: 10.1111/j.1476-5381.1989.tb16885.x
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of haemorrhagic shock in rats by cholinomimetic drugs

Abstract: 1 In an experimental model of haemorrhagic shock resulting in the death of all rats within 20-30min, the intravenous (i.v.) injection of the tertiary amine cholinesterase inhibitor physostigmine (17-701pgkg-1) induced a prompt, sustained and dose-dependent improvement of cardiovascular and respiratory function, with marked increase in the volume of circulating blood and survival of all treated animals, at least for the 2 h of observation. 2 Similar results were obtained with the i.v. injection of the cholinoce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…choline in the haemorrhaged rats was mediated solely by central nicotinic receptors. It has recently been reported that intravenous administration of oxotremorine or physostigmine restores blood pressure and increases the survival rate in haemorrhaged rats (Guarini et al, 1989), an effect also mediated by central nicotinic receptors. The present results are in good accordance with this report.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…choline in the haemorrhaged rats was mediated solely by central nicotinic receptors. It has recently been reported that intravenous administration of oxotremorine or physostigmine restores blood pressure and increases the survival rate in haemorrhaged rats (Guarini et al, 1989), an effect also mediated by central nicotinic receptors. The present results are in good accordance with this report.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological activation of brain cholinergic neurotransmission results in an increase in blood pressure in several vertebrate species, including rat, dog and man (Brezenoff & Guiliano, 1982). More recently, it has been reported that the centrally acting drugs, oxotremorine and physostigmine, can restore blood pressure and increased survival rate of rats in an experimental haemorrhagic shock model (Guarini et al, 1989). Based on these observations it has been suggested that an increase in central cholinergic tone is involved in the development and maintenance of hypertension (Brezenoff, 1984), while a decrease in central cholinergic tone is involved in the complex pathophysiology of cardiovascular shock (Guarini et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…not significantly different) in all experimental groups. As previously described (Bertolini et al, 1986a,b,c;1989;Guarini et al, 1989;1990b), the acute hypovolaemia induced in our model of volume-controlled haemorrhagic shock in anaethetized rats was incompatible with survival, all salinetreated animals dying within 26 ± 3 min after treatment. On the other hand, and again in agreement with previous results (Bertolini et al, 1986a,b,c;1989;Guarini et al, 1990a,b,c), the timely i.v.…”
Section: Animals and Surgerymentioning
confidence: 93%
“…acetylcholine itself, carbachol, oxotremorine or indirectly acting cholinergic agents, including the acetylcholine precursor choline and the acetylcholinesterase inhibitors physostigmine and neostigmine, increase blood pressure by activating central cholinergic mechanisms in conscious and anaesthetised animals [1,[3][4][5][6]. Recent studies reported that the centrally acting cholinergic drugs including choline, oxotremorine and physostigmine can restore blood pressure and increase the survival rate of rats under several hypotensive conditions such as experimental haemorrhagic shock [7][8][9], endotoxic shock [10], spinal shock [11] or even after prolonged respiratory arrest [12]. Observations from these experiments suggested that a decrease in central cholinergic tone is involved in the complex pathophysiology of shock.…”
Section: Introductionmentioning
confidence: 99%